The basics of performance measurement - Harbour, Jerry L. (Boca Raton : CRC Press, 2009)
The book provides a six step method for developing a performance measurement system. It shows how to design performance measurement families and how to build hierarchies tailored to different levels within an organization. It also covers collection and distribution as well as the value of performance measure displays.
Performance measurement -- Types of performance measures -- A family of measures -- Performance measurement hierarchies -- Units of measurement -- Collection and distribution -- Performance measure displays -- Interpretation and action -- Putting it all together.
"A Productivity Press book."
Includes bibliographical references and index.
nmn 24/05/13
Loans
Keywords: Performance standards; Performance -- Evaluation